The Effect of Bilingual Congruence on the Persuasive Influence of Videos and Comments on YouTube. (June 2018) - Walther, Joseph B.; Neubaum, German; Rösner, Leonie; Winter, Stephan; Krämer, Nicole C.
Social media offer a global village in which user-generated comments from different groups and many languages appear. Extending the notion of prototypes in social identification theory, research examined the persuasive influence of comments supporting or deriding a public service announcement video on YouTube, where comments' language either matched or differed from the videos'. Bilingual participants watched videos in English or Mandarin Chinese promoting water conservation, accompanied by comments in English or Mandarin that supported or derided the videos' message. Results replicated previous findings about the valence of comments on public service announcement evaluations, overridden by an interaction between valence and language congruity: Comments in the same language as the videos' affected readers' evaluations of the video more than did comments in the language other than the videos'.